Literasi Ekonomi dan Keuangan Syariah bagi Santriwati di Pondok Pesantren Al Falah Puteri Banjarbaru - Mukhlis Kaspul Anwar; Muhammad Yulian Ma'mun; Lola Malihah; Ahmad Taufiq; Mera Murliana; Dewi Maharani (ABDI MAKARTI, 2022)
This community service aims to provide knowledge and skillset for the pesantren community to make well-informed and wise decisions regarding Islamic financial matters. This program was conducted at the Al Falah Islamic Boarding School for Girls (Pondok Pesantren Al Falah Puteri) in Banjarbaru. The target audience of this campaign is 12th-grade students majoring in social sciences. A total of 35 female students that were representatives from 3 different classrooms, took part in this program. Lecturers of the Islamic Banking Department, Islamic Institute of Darussalam Martapura, acted as speakers at this event. The material they deliver relates to the economy in general, a glance of Islamic economics, and introduction to Islamic financial institutions. Discussion and Q & A sessions were held as an addition to this presentation to enrich the understanding and insights of financial literacy. It was seen that the students were very excited about involving in the discussion, especially when discourse the differences between conventional economics and Islamic economics. The enthusiasm of the participants showed that they were aware of the importance of understanding Islamic economics and Islamic finance in their life.